Perspectives and tasks in horticultural production - Papp, J.; Nyéki, J. (International Journal of Horticultural Science, 2002)
The work summarizes the prospective conceptions of all the five horticultural branches. These branches (vegetable, fruit, grape and wine, herb and ornamental plant production) with the production of propagating material together amount to round 30-35% of the total value of the entire plant production. The performance of horticultural branches declined significantly because of privatisation and lack of capital. The accession to the EU urges the development of modernization and competitiveness, therefore the state subsidies are indispensable.